(untitled) (Third Sector Social Economic Review, 2025)
This research was conducted to measure the trade union awareness of students studying at the Faculty of Economics and Administrative Sciences and the Faculty of Business Administration at Karabük University. In this context, it aims to determine whether students have previously heard of the concept of trade unions based on their socio-demographic characteristics and to explore their thoughts on joining a trade union after graduation. This quantitative study, based on the questionnaire method, includes a student population where nearly half are foreigner, while slightly more than half are Turkish students. The research was conducted in two phases: the first phase included 540 students, and the second phase focused on 396 students who were familiar with the concept of unions. The collected data were analyzed using the EXCEL program, considering theories on union attitudes among trade young people before entering the labor market. According to the research findings, approximately three-quarters of the 540 students had previously heard of the concept of unions, and 39% considered joining a union after graduation. Among the 396 students who were aware of unions, 53.2% expressed an intention to become union members. The awareness of unions increased as students progressed in their academic levels; however, the same increase is not reflected in the thought of being unionized. Turkish students were more familiar with the concept of unions and had a greater intention to join unions compared to foreigner students. However, among those who had heard of unions, the intention to join varied based on nationality. Additionally, having unionized employees in their families and social circles significantly increased students’ inclination toward union membership. The study provides several recommendations for trade unions and universities to develop different strategies to enhance trade union awareness among students.